2016
DOI: 10.1016/j.bpj.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Binding and Oligomerization of the Lipopeptide A54145 Studied by Pyrene Fluorescence

Abstract: A54145 is a lipopeptide antibiotic related to daptomycin that permeabilizes bacterial cell membranes. Its action requires both calcium and phosphatidylglycerol in the target membrane, and it is accompanied by the formation of membrane-associated oligomers. We here probed the interaction of A54145 with model membranes composed of dimyristoylphosphatidylcholine and dimyristoylphosphatidylglycerol, using the steady-state and time-resolved fluorescence of a pyrene-labeled derivative (Py-A54145). In solution, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…The figure also includes the key findings of another recent study, in which pyrene moieties were semisynthetically incorporated into the fatty acyl tail of A54145 [16]. As in the current study, two successive calcium-dependent transitions were observed, which occurred at calcium concentrations very similar to those reported here.…”
Section: Discussionsupporting
confidence: 68%
“…The figure also includes the key findings of another recent study, in which pyrene moieties were semisynthetically incorporated into the fatty acyl tail of A54145 [16]. As in the current study, two successive calcium-dependent transitions were observed, which occurred at calcium concentrations very similar to those reported here.…”
Section: Discussionsupporting
confidence: 68%
“…Intriguingly, global analysis of time-resolved excimer fluorescence indicates that, even at partial Ca 2+ saturation, membrane-bound A54145 already exists as an oligomer, which however has a lower number of subunits that the one observed at full saturation. 84 This observation may be related to the proposed occurrence of daptomycin tetramers as intermediates of pore formation (see Figure 6). In this context, it is also worth mentioning that daptomycin may interact with membranes even in the absence of calcium, as shown by fluorescence polarization anisotropy in an early study, 38 although this observation does not indicate oligomer formation.…”
Section: Topology Of Membrane-associated Daptomycinmentioning
confidence: 87%
“…85 Proximity also exists between the fatty acyl tails of adjacent oligomer subunits. This is evident from the excimer fluorescence of perylene or pyrene incorporated into the acyl residues of daptomycin 51 and A54145, 84 respectively (see Figure 7). In spite of their direct attachment to Trp (1) , excimer fluorescence-and thus, aggregation of fatty acyl residues-arises already in the partially Ca 2+ -saturated state, 84 while Trp (1) responds only at full Ca 2+ saturation.…”
Section: Topology Of Membrane-associated Daptomycinmentioning
confidence: 95%
See 2 more Smart Citations